IMPLEMENTASI PENERTIBAN BANGUNAN LIAR DI RUANG TERBUKA HIJAU KABUPATEN KARIMUN - Ramadhani, Bella Suci; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Implementation Demolition Of Illegal Buildings at The Green Open Spaces District Of Karimun. Green open spaces have benefits of the high life. Vorious functions related to the existence not only in improving the quality of the environment and for the subtainability of the area but also can be a city of pride and identity. The control of illegal buildings is still not optimal. This can be seen from many illegal buildings were estabilished in the forbidden region in the regulation of spatial plan district of Karimun as green open spaces, riparian, riparian lakes, parks, side walks, and other public facilities. Purpose of this study to analyze the implementation demolition of illegal buildings at the green open spaces district of Karimun and to identify factors – factors that influence. This research uses descriptive qualitative method, techniques of data collection is through observation and interviews in which the people involved in the implementation of the policy as informans. This study uses the theory of Van Meter and Van Horn.The result of this study indicate that the implementation demolition of illegal buildings at karimun district green open spaces has not run optimally although the standard, goals and objectives of the policy are clear, sufficient number of policy implementers, coordination and communication among agencies has been running good as well as the performance of duties of executor is in compliance with applicable rules. In the control run by executing warrant and granted and also supporting operational facilities inadequate. It is also the response and participation of the community in the area enforcement is low. Even there are still people who do not care about the local regulations applicable.Keywords : implementation, demolition, illegal buildings, green open spaces